Efeito da moxidectina sobre o comportamento tipo depressivo e ansioso em camundongos swiss - Schneider, Gregory Klein (2024)
Major Depressive Disorder (MDD) affects approximately 6% of the population, but its pathophysiology and pharmacotherapy remain poorly elucidated. Monoaminergic antidepressants have as their main mechanism of action interference with the metabolism and reuptake of monoamines. These drugs consistently ameliorate severe symptoms in patients, but their clinical success rate is less than 67%. Furthermore, these drugs may take weeks to show effect. Therefore, the discovery of new pharmacological targets, as well as new possible treatments, have been explored with the aim of improving prognosis. In this context, moxidectin, an originally endectocidal drug, has shown antidepressant activity in rats. Its mechanism of action is speculated to be related to the positive allosteric modulation of GABAA receptors and activation of P2X4, nicotinic α7 and glycine receptors. Thus, the objectives of this study are to compose a bibliographic review on the literature spanning 2013 to 2023 regarding the characteristics of moxidectin as a neuromodulator; and investigate the potential antidepressant and anxiolytic effect of a single dose of moxidectin (1.5 mg/kg) in male Swiss mice, as well as its effect on oxidative stress markers and molecular parameters. The assessment of depressive-anxious-type behaviors was carried out using the tail suspension (TST), splash (SPT), elevated plus maze (EPM) and open field (OFT) tests, which revealed a decrease in depressive-type behavior, represented by shorter immobility time in TST and longer grooming time in SPT, and anxiogenesis, represented by longer time spent in the center in OFT. To better elucidate the biological basis of the observed behavioral changes, oxidative tests assays demonstrated an increase in Glutathione S-transferase (GST) and total antioxidant capacity (TAC) in the prefrontal cortex and a decrease in GST in the hippocampus of the animals, without changes in substances reactive to the thiobarbituric acid (TBARS). rt-PCR demonstrated an increase in Brain-Derived Neurotrophic Factor (BDNF) mRNA in the cortex. The results presented in this work demonstrate that the literature consistently presents moxidectin as capable of inducing improvement in the behavior of animal submitted to models of neuropsychopathologies, has a favorable toxicological profile and, in our protocol, a single dose of moxidectin was able to reduce depressive-like behavior in mice without negatively impacting oxidative stress parameters, in addition to inducing an increase in BDNF mRNA in neural tissue. These are promising results that encourage the continuation of the study of moxidectin as a possible new compound in the treatment of MDD.